PELATIHAN PEMBUATAN VIDEO SIMULASI PERNIKAHAN DIMASA PANDEMI COVID-19 - Muhammad Alfin; Suprihatin Suprihatin; Agus Supriyanto (LPPM Universitas Islam 45, 2022)
The Covid-19 pandemic is still endemic in the beloved country of Indonesia, this incident greatly affects all aspects so that many changes must be made in order to continue to implement and continue to implement the Health Protocol. One of them is marriage, but the public, especially the bride and groom, do not know what to do in a wedding during the Covid-19 pandemic. The method used is training for the bride and groom through videos that have been made. The results in carrying out this activity are expected to add insight and description for the bride and groom to carry out wedding activities during the covid pandemic.